Tuning the Refractive Index and Optical Band Gap of Silk Fibroin Films by Electron Irradiation - S. Asha; Y. Sangappa; Sanjeev Ganesh (Journal of Spectroscopy)
The Bombyx mori silk fibroin (SF) films were prepared by solution casting method and effects of electron beam on the optical properties and optical constants of the films have been studied by using UV-Visible spectrophotometer. Optical properties like optical band gap Eg, refractive index n, extinction coefficient k, optical conductivity σopt, and dielectric constants ε∗ of virgin and electron irradiated films were determined by using UV-Visible absorption and transmission spectra. It was found that the reduction in optical band gap and increase in refractive index with increasing radiation dosage was observed. It is also observed from results that there is increase in dielectric constants with increasing photon energy. The observed optical changes have been tried to be correlated with the structural changes, revealed through FT-IR spectroscopy. The present study is quite important for tailoring the optical responses of SF films as per specific requirements.